EDUKASI OBESITAS SEBAGAI UPAYA PREVENTIF PENYAKIT METABOLIK PADA USIA PRODUKTIF DI DESA POJOK KEDIRI - Dita Apriana Dwi Astuti; Aprilia Anjarwati; Rochmad Krissanjaya; Saiful Muttaqin; Elfred Rinaldo Kasimo (FIP UNIRA MALANG, 2026)
Obesity is one of the major risk factors for metabolic diseases such as type 2 diabetes mellitus, hypertension, dyslipidemia, and cardiovascular disease, particularly among the productive-age population. The increasing prevalence of obesity in the community indicates the need for promotive and preventive efforts through health education. This Community Service Program aimed to improve the knowledge and awareness of productive-age individuals regarding obesity as a risk factor for metabolic diseases and to encourage the adoption of healthy lifestyles in Pojok Village, Kediri. The program was conducted through health counseling, interactive discussions, and anthropometric assessments, including measurements of body weight, height, and Body Mass Index (BMI) calculation among 47 participants. The results showed that the majority of participants were female (72.3%). Based on BMI classification, 31 participants (65.96%) were categorized as obese, 11 participants (23.40%) as overweight, and only 5 participants (10.64%) had normal BMI status. These findings indicate a high risk of metabolic disorders among the productive-age population in the intervention area. The educational activities received positive responses and improved participants’ understanding of the importance of balanced nutrition, regular physical activity, and routine body weight monitoring. In conclusion, obesity education through the Community Service Program was effective as an initial preventive strategy to improve public health literacy and reduce the risk of metabolic diseases.